2022
DOI: 10.3390/ijerph192315758
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition and Fitness Characteristics of Firefighters Participating in a Health and Wellness Program: Relationships and Descriptive Data

Abstract: This study investigated body composition and fitness test relationships from firefighters participating in a health and wellness program and categorized firefighters according to population norms relative to sex and age. Data from 270 firefighters (men = 258, women = 12) were analyzed, including body composition (body mass index [BMI], body fat percentage [BF%], waist circumference [WC], waist-to-hip ratio) and fitness (sit-and-reach, grip strength, leg press, crunches, push-ups, maximal aerobic capacity [V̇O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 70 publications
2
25
0
Order By: Relevance
“…The present investigation has demonstrated that the Equivital and Black Ghost software is an accurate, noninvasive, and safe method of estimating core body temperature in healthy young adults. Future investigations should ensure adequate age diversity within their samples to improve the generalizability of these ndings considering the diverse age, tness, and health characteristics of current United States re ghters [52]. We believe a strength of the present investigation is the representation of females in re ghter research and encourage future investigations to continue this effort to maintain representation and rigor proposed by the National Health Institute [53].…”
Section: Discussionmentioning
confidence: 81%
“…The present investigation has demonstrated that the Equivital and Black Ghost software is an accurate, noninvasive, and safe method of estimating core body temperature in healthy young adults. Future investigations should ensure adequate age diversity within their samples to improve the generalizability of these ndings considering the diverse age, tness, and health characteristics of current United States re ghters [52]. We believe a strength of the present investigation is the representation of females in re ghter research and encourage future investigations to continue this effort to maintain representation and rigor proposed by the National Health Institute [53].…”
Section: Discussionmentioning
confidence: 81%
“…Increased BF% and BM index have been associated with lower physical fitness 55 and increased risk for cardiovascular disease 56 in firefighting populations. As shown in Figures 1 and 2, BF%, BM, FM, chest skinfold girth, and thigh skinfold girth did not significantly change during the training academy.…”
Section: Discussionmentioning
confidence: 99%
“…Grip Strength. Grip strength was measured by means of a handgrip dynamometer (Lafayette Instrument, Lafayette, IN) using procedures previously described in the literature (1), which have also been adopted in first responder fitness testing (28)(29)(30)(31). The handle was set to the middle phalanx of the middle finger positioned straight across the front of the handle.…”
Section: Methodsmentioning
confidence: 99%
“…Leg Press. A plate-loaded 45°leg press machine (Cybex, Owatonna, MN) was used to perform a 1-repetition maximum (1RM) test to measure lower-body strength (31,40). Department-specific procedures were used for this test within the health and wellness program (31).…”
Section: Methodsmentioning
confidence: 99%